Interest rate reforms and firm performance in Bangladesh’s manufacturing sector - Rahman, Nusrat; Harun, Md Yousuf (Asian Economic and Financial Review, 2025)
The study investigates the effects of a single-digit (6%–9%) interest rate set by the Bangladesh Bank in 2020, involving 94 listed manufacturing companies across 10 industries from 2018 to 2023. The key objective of the research is to examine the impact of such interest rate reform on financial performance, proxied by Return on Assets (ROA), Return on Equity (ROE), and Market-to-Book (M/B) ratio. Fixed and random effects panel data analysis techniques and the system generalized method of moments (GMM) have been applied to address heteroskedasticity, autocorrelation, and endogeneity. The results show that lower interest rates improve ROA and ROE, especially for capital-intensive industries like textiles and engineering, because of reduced borrowing costs. Higher lending rates and debt leverage adversely affect the M/B ratio, indicating that investors are concerned about the increase in debt levels. Price fluctuations in the exchange rate affect firm performance, which relies on imports. Additionally, firms with larger sizes and higher GDP growth perform better in the market. The study highlights the need for a dynamic and sector-focused interest rate policy to improve the resilience of the manufacturing sector, as well as strategies like capacity building in financial management to ensure long-term sustainability. To address the limitations of this study, future research should use probability sampling together with unlisted firm data and combine primary and secondary data while expanding the study period after the post-pandemic period. Moreover, cross-industry analysis will help achieve a better understanding of long-term interest rate effects on manufacturing firm performance.